2018
DOI: 10.1536/ihj.17-179
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Percutaneous Coronary Intervention for Significant Atherosclerotic Lesions in Segment Proximal to Myocardial Bridge at Left Anterior Descending Coronary Artery

Abstract: This study aimed to evaluate the efficacy of percutaneous coronary intervention (PCI) for significant atherosclerosis lesions proximal to myocardial bridge (MB) at left anterior descending coronary artery (LAD).A total of 330 consecutive patients with LAD significant stenosis, diagnosed as acute coronary syndrome (ACS), were included. Based on whether combined with MB, the patients were divided into the MB group (MB, n = 48) and non-MB group (NMB, n = 282). Drug eluting stents (DES) were successfully implanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Other studies have also shown significant lumen obstruction in the segments proximal to myocardial bridge to also have higher chances of re-stenosis and the occurrence of an increased amount of MACEs following PCI with drug eluting stents [15] …”
Section: Discussionmentioning
confidence: 98%
“…Other studies have also shown significant lumen obstruction in the segments proximal to myocardial bridge to also have higher chances of re-stenosis and the occurrence of an increased amount of MACEs following PCI with drug eluting stents [15] …”
Section: Discussionmentioning
confidence: 98%
“…Stent into the MB segment could lead to a high rate of coronary artery perforation, stent restenosis, and stent fracture, etc. 25 – 27 . However, there are some conditions where a stent is required to wholly or partially cover the MB.…”
Section: Discussionmentioning
confidence: 99%
“…For such lesion, the most direct way is to implant 2 stents from the normal distal segment to the normal proximal segment of the lesion. However, from the perspective of long-term prognosis, the effect of stents implantation at the myocardial bridge is not good [ 2 ], but if the stents aren’t implanted completely, residual angina attack may still occur. Therefore, the strategy of stent implantation is very important and tricky.…”
Section: Discussionmentioning
confidence: 99%